1981
DOI: 10.1002/j.1537-2197.1981.tb07816.x
|View full text |Cite
|
Sign up to set email alerts
|

Nectar Production, Composition, Energetics and Pollinator Attractiveness in Spring Flowers of Western New York

Abstract: High Performance Liquid Chromatography (HPLC) was used to determine specific sugar ratios (fructose, glucose and sucrose) in nectars of nine families of flowering plants. All nectars contained all three sugars with the exception of that of Asclepias. Asclepias nectar was nearly a pure sucrose solution. Sucrose/hexose ratio was correlated with flower morphology, with tubular flowers having more sucrose and open flowers having more hexose. Open flowers contained nectar whose concentration was more affected by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
5

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 22 publications
2
37
0
5
Order By: Relevance
“…Experimental changes in ambicnt relative humidity have no effect on the amount of sugars secreted hy extrafloral nectaries of Aüanthus but modify the volume of the nectar drop (Bory, 1983). Recent studies have shown that there is a significant negative correlation hetwccn nectar solute concentration and relative humidity ; the drier air, the more concentrated the nectar (Corbet, 1978 ;Southwick et al, 1981 ;Pleasants, 1983 ;Corbet and Delfosse, 1984).…”
Section: B -Variations Occuring Undcr Controllcd Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental changes in ambicnt relative humidity have no effect on the amount of sugars secreted hy extrafloral nectaries of Aüanthus but modify the volume of the nectar drop (Bory, 1983). Recent studies have shown that there is a significant negative correlation hetwccn nectar solute concentration and relative humidity ; the drier air, the more concentrated the nectar (Corbet, 1978 ;Southwick et al, 1981 ;Pleasants, 1983 ;Corbet and Delfosse, 1984).…”
Section: B -Variations Occuring Undcr Controllcd Conditionsmentioning
confidence: 99%
“…The effects of different factors (microc1imatic conditions, flower age, time of the day, nectar removal. .. ) influencing the nectar production rate and the sugar concentration of the nectar have hcen also quantitativcly investigated (Thyri, 1978 ;Baker and llaker, 1979;Corbet et al, 1979a and b;Brink and De Wct, 1980;Southwick et al, 1981 ;Plcasants, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…They display various features to attract pollinators such as flower color, shape, and odor (Raguso 2004). Flowers also provide nectar and pollen as rewards (Southwick et al 1981;Waser 1986). For bees, they represent unique food sources for both adults and larvae (Michener 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Quantidade, concentração e teor de açúcares encontrados no néctar, dão parâmetros para estabelecer o seu nicho trófico e, por isso, são discutidos por vários autores como agentes determinantes de atração alimentar, assim como a distinção que é feita por esses insetos quando da coleta do mesmo (Heinrich & Raven, 1972;Corbet & Wilmer, 1981;Southwick et al, 1981;Baker & Baker, 1983;Gottsberger et al, 1984;Roubik & Buchmann, 1984;Real & Rathcke, 1991).…”
Section: Introductionunclassified